Selection and satisfaction criteria of temporary work agency as a service provider in Finland and Norway - Venäläinen, Annika (My University, 2023)
In recent years, the acquisition of professional services has become increasingly relevant for value creation within companies. This growing trend of outsourcing has also been observed in the Nordic countries, where temporary work has grown rapidly to become a significant feature of many national labor markets. The utilization of employment intermediaries such as temporary work agencies has become an increasingly important area of research within the field of human resource management. This study contributes to advancing the understanding of partner selection criteria in the context of temporary work agencies and aims to broaden the existing knowledge regarding the perceptions of organizations’ utilization of TWA. The main purpose of the study is to determine the most important selection criteria for a company’s choice of temporary work agency as a service provider and the criteria for client companies’ satisfaction with the chosen agency. Specifically, this research examines the selection criteria and the satisfaction in the context of Finland and Norway and aims to comprehend whether the home country of the client company makes a difference. The theory and main concepts are derived from previous literature and research on professional service providers. The theoretical framework consists of the importance of temporary work agency and prior research on the reasons for the utilization of TWA, the professional service provider selection process, the selection criteria and the criteria related to the client’s satisfaction with the service provider. The study examines two TWAs operating in both Finland and Norway, and a quantitative research method is employed. All together 45 Norwegian and 10 Finnish clients answered an online survey via Webropol. The study excluded those who initiated cooperation through a lengthy bidding process. The data was collected in spring of 2023 and analyzed in IBM SPSS statistics software version 28. The findings suggest that the primary motivations for utilizing a TWA are avoiding the hiring process, flexibility through on-demand workforce, substituting for absences, and preventing mis-recruitments. Respectively, the most significant selection criteria identified are the agency's ability to meet expectations, understand client needs, deliver quality service and offer flexibility. Regarding client satisfaction, the study reveals that several criteria impact the satisfaction with a TWA, including the ability to handle complaints, to meet or exceed expectations, adhere to agreed timelines and offer creative solutions and demonstrate accuracy. While statistical power limitations prevented a robust analysis, some differences emerged between the Finnish and Norwegian clients. The Finnish respondents placed a greater emphasis on avoiding the hiring process, cost of service, and service quality compared to their Norwegian counterparts. Additionally, the Finnish clients reported higher satisfaction with accuracy, whereas Norwegian clients expressed higher satisfaction with adherence to schedules.

Viime vuosina asiantuntijapalvelujen hankinnasta on tullut yhä tärkeämpää yritysten arvonluonnin kannalta. Ulkoistamisen kasvava suuntaus on havaittu myös Pohjoismaissa, joissa vuokratyö on kasvanut nopeasti ja siitä on tullut merkittävä tekijä monilla kansallisilla työmarkkinoilla. Vuokratyövoiman käytöstä on tullut yhä tärkeämpi tutkimusalue henkilöstöhallinnon alalla. Tämä tutkimus edistää osaltaan kumppanien valintakriteerien sekä tyytyväisyyteen vaikuttavien tekijöiden ymmärtämistä vuokratyövoimaa välittävien yritysten kontekstissa. Tutkimuksen päätarkoituksena on selvittää tärkeimmät valintaperusteet, joiden perusteella yritykset valitsevat vuokratyövoimaa välittävän yrityksen palveluntarjoajaksi, sekä kriteerit, joiden perusteella asiakasyritykset ovat tyytyväisiä valittuun yritykseen. Tässä tutkimuksessa tarkastellaan erityisesti valintaperusteita ja tyytyväisyyttä Suomen ja Norjan olosuhteissa, ja pyritään ymmärtämään, onko asiakasyrityksen kotimaalla merkitystä. Teoria ja keskeiset käsitteet on johdettu aiemmasta kirjallisuudesta ja tutkimuksista, jotka käsittelevät ammatillista palveluntarjontaa. Teoreettinen viitekehys koostuu vuokratyövoiman vuokrausyritysten merkityksestä sekä aiemmasta tutkimuksesta. Olemassa olevan kirjallisuuden pohjalta tässä työssä tarkastellaan vuokratyövoiman käytön syitä, ammatillisen palveluntarjoajan valintaprosessia ja valintakriteerejä sekä kriteerejä, jotka liittyvät asiakkaan tyytyväisyyteen palveluntarjoajaa kohtaan. Tutkimuksessa tarkastellaan kahta Suomessa ja Norjassa toimivaa vuokratyöyritystä, ja siinä hyödynnetään kvantitatiivista tutkimusmenetelmää. Tutkimukseen osallistui 45 asiakasta Norjasta ja 10 Suomesta. He vastasivat Webropolin kautta tehtyyn verkkokyselyyn. Kysely lähetettiin kaikille maiden asiakkaille lukuun ottamatta niitä asiakkaita, jotka aloittivat yhteistyön pitkällisen tarjousmenettelyn kautta. Tiedot kerättiin keväällä 2023 ja analysoitiin IBM SPSS 28 -ohjelmistolla. Tulosten mukaan vuokratyövoimayrityksen käytön tärkeimpiä syitä ovat rekrytointiprosessin välttäminen, joustavuus kysynnän mukaan palkatun työvoiman avulla, poissaolojen korvaaminen ja virheellisten rekrytointien estäminen. Merkittävimmiksi valintakriteereiksi nousi vuokratyöyrityksen kyky vastata odotuksiin, ymmärtää asiakkaan tarpeita, tarjota laadukasta palvelua ja olla joustava. Asiakastyytyväisyyden osalta tutkimus paljastaa, että vuokratyövoimayrityksen käytön tyytyväisyyteen vaikuttavat useat kriteerit, kuten yrityksen kyky käsitellä valituksia, täyttää tai ylittää odotukset, noudattaa sovittuja aikatauluja, tarjota luovia ratkaisuja ja osoittaa tarkkuutta. Vaikka tilastolliset rajoitukset estivät luotettavan analyysin tekemisen, suomalaisten ja norjalaisten asiakkaiden välillä ilmeni joitakin eroja. Suomalaiset vastaajat painottivat norjalaisiin vastaajiin verrattuna enemmän rekrytointiprosessin välttämistä, palvelun kustannuksia ja palvelun laatua. Lisäksi suomalaiset asiakkaat ilmoittivat olevansa tyytyväisempiä tarkkuuteen, kun taas norjalaiset asiakkaat olivat tyytyväisempiä aikataulujen noudattamiseen.
Keywords: vuokratyö; valintakriteerit; tyytyväisyys; fi=Kansainvälinen liiketoiminta|en=International Business|; Master's Degree Programme in International Business